Preliminary molecular work on hard clam, meretrix lyrata from Buntal Bay, Sarawak - Wong, Fong Fun (Universiti Malaysia Sarawak, UNIMAS, 2009)
Meretrix lyrata (lyrate Asiatic hard clam) could be found at Buntal Bay, Sarawak. This species is a filter feeder so it play important role in balancing aquatic ecosystem besides its important role as protein sources to coastal communities. Studies on M. lyrata in Sarawak had been limited to the morphological documentation and ecology. This study was designed to obtained baseline molecular data for M. lyrata from Buntal Bay, Sarawak. Standard molecular protocols were employed namely total genomic DNA extraction, Polymerase Chain Reaction (PCR), PCR product purification, Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) and direct sequencing. In addition, PCR product also subjected to PCR-RFLP. The 16S rRNA (approximately 650bp) and ITS region (approximately 1400bp) had been successfully amplified from M. lyrata. PCR-RFLP profile had also been documented by digestion of ITS PCR product with six different enzymes namely Csp 6I, Hind III, Taq I, Mbo II, BsuR I and Mn II .Based on ITS sequences, the genetic distance between individual found in Buntal area ranged between 0% and 0.3%. Low genetic distance was observed between M. lyrata from Buntal and China which ranged between 0.3% and 0.7%.